Postpartum Remote Health Coaching Intervention for Individuals With a Hypertensive Disorder of Pregnancy: Proof-of-Concept Study - Jaclyn D Borrowman; Lucas J Carr; Gary L Pierce; William T Story; Bethany Barone Gibbs; Kara M Whitaker (JMIR Formative Research)
Abstract BackgroundCardiovascular disease (CVD) is the leading cause of death among women in America. Hypertensive disorders of pregnancy (HDP) negatively impact acute and long-term cardiovascular health, with approximately 16% of all pregnancies affected. With CVD 2‐4 times more likely after HDP compared to normotensive pregnancies, effective interventions to promote cardiovascular health are imperative. ObjectiveWith postpartum physical activity (PA) interventions after HDP as an underexplored preventative strategy, we aimed in this study to assess (1) the feasibility and acceptability of a remotely delivered PA intervention for individuals with HDP 3‐6 months postpartum and (2) changes in average steps per day, skills related to PA behavior, and postpartum blood pressure (BP). MethodsA remotely delivered 14-week health coaching intervention was designed based on prior formative work. The health coaching intervention called the Hypertensive Disorders of Pregnancy Postpartum Exercise (HyPE) intervention was tested for feasibility and acceptability with a single-arm proof-of-concept study design. A total of 19 women who were 3‐6 months postpartum HDP; currently inactive; 18 years of age or older; resided in Iowa; and without diabetes, kidney disease, and CVD were enrolled. Feasibility was assessed by the number of sessions attended and acceptability by self-reported satisfaction with the program. Changes in steps achieved per day were measured with an activPAL4 micro, PA behavior skills via validated surveys online, and BP was assessed remotely with a research-grade Omron Series 5 (Omron Corporation) BP monitor. ResultsParticipants at enrollment were on average 30.3 years of age, 4.1 months postpartum, self-identified as non-Hispanic White (14/17, 82%), in a committed relationship (16/17, 94%), and had a bachelor’s degree (9/17, 53%). A total of 140 of 152 possible health coaching sessions were attended by those who started the intervention (n=19, 92%). Intervention completers (n=17) indicated they were satisfied with the program (n=17, 100%) and would recommend it to others (n=17, 100%). No significant changes in activPAL measured steps were observed from pre- to posttesting (mean 138.40, SD 129.40 steps/day; PPPgPgP ConclusionsWhile PA behaviors did not change, the intervention was found to be feasible and acceptable among this sample of at-risk women. After additional refinement, the intervention should be retested among a larger, more diverse, and less physically active sample.